PENGUNGKAPAN MANAJEMEN RISIKO PERUSAHAAN DAN MODAL INTELEKTUAL PADA NILAI PERUSAHAAN - Mulyono, Helena Elvoni Putri; Lindrawati, Lindrawati (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The company was founded with the aim of obtaining maximum profit, developing business, competing competitively in rapid technological developments and being able to maintain company value. Companies need to carry out effective and efficient operations to maintain company value by managing their resources, one of which is intellectual capital. Knowledge of intellectual capital provides a competitive advantage for the company. In addition, companies need risk management disclosures that can have an influence on market views, so companies can manage risks and minimize existing risks. This has an impact on decision making by investors. This study aims to analyze the effect of corporate risk management disclosure and intellectual capital on firm value. The research design used is quantitative research and used data namely annual reports and stock prices. The object of research is manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression. The result of this study is that the enterprise risk management disclosure has a negative effect on firm value, where the more disclosure of enterprise risk management makes investor increasingly avoid the company so that the frim value decreasing. Intellectual capital has no effect on the value of the company, indicating that the intellectual capital owned by the company is not considered by investors so that it does not affect the value of the company